Revision of the Mesoamerican Genus Cataractocoris Usinger (Hemiptera: Heteroptera: Nepomorpha: Naucoridae) - Sites, Robert W.; Reynoso-Velasco, Daniel; Novelo-Gutiérrez, Rodolfo (Zootaxa, 2013)
The genus Cataractocoris includes large waterfall-inhabiting insects that occur from Mexico to El Salvador and has re-ceived very little attention in the literature. Based on extensive field work during the past three years, we have collected saucer bugs (Heteroptera: Naucoridae) from many localities in central and southern Mexico. We here present detailed dis-tributions and diagnostic information of the two described species of Cataractocoris and the description of a third species that occurs from Nayarit state in Mexico south to Guatemala. An illustrated taxonomic key to identify the species also is presented.